2019
DOI: 10.1155/2019/4863182
|View full text |Cite
|
Sign up to set email alerts
|

KIF20A Affects the Prognosis of Bladder Cancer by Promoting the Proliferation and Metastasis of Bladder Cancer Cells

Abstract: Objective. To investigate the expression of kinesin family member 20A (KIF20A) in bladder cancer, the effect of KIF20A on the proliferation and metastasis of bladder cancer cells, and the effect of KIF20A expression on the prognosis of bladder cancer patients. Methods. Bladder cancer tissue and its adjacent tissues were collected from tumour patients. The mRNA and protein expression levels of KIF20A in the tissue samples were detected by qRT-PCR and western blot. Immunohistochemical (IHC) staining was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…These two proteins account for approximately 10% of the total interactions, which means that these two proteins may contribute considerably to the difference in brown eggshell coloration. Both proteins are known to play a role in cell mitosis and cell proliferation [29,30].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…These two proteins account for approximately 10% of the total interactions, which means that these two proteins may contribute considerably to the difference in brown eggshell coloration. Both proteins are known to play a role in cell mitosis and cell proliferation [29,30].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Nevertheless, until now, there have only been a few reports about KIF11 [72] and KIF2C [66] in BCa. Recently, Shen et al observed that overexpression of KIF20A in BCa is associated with poor prognosis and worse tumor differentiation [73]. CDC20 serves as a critical protein in the spindle assembly checkpoint, cell cycle progression, and mitosis [74].…”
Section: The Hub Genes Potentially Associated With the Clinical Prognmentioning
confidence: 99%
“…e time of diagnosis plays a crucial role in achieving a good prognosis. erefore, determination of new molecular markers that act as potential therapeutic targets and prognostic indicators of BC is vital for conducting a clinically accurate diagnosis and treatment [3,4].…”
Section: Introductionmentioning
confidence: 99%